An Exploration of Elementary School Teachers' Experiences in Integrating Artificial Intelligence (AI) as a Digital Learning Medium - Ribi Nava Aulia Mukti; Nurul Hidayatis Sa’diya; Agung Setyawan (Penerbit Presisi Pustaka, 2025)
This study explores the experiences of elementary school teachers in integrating Artificial Intelligence (AI) as a digital learning medium. The research aims to identify teachers’ perceptions, challenges, and strategies in adopting AI-based tools to enhance the teaching and learning process. Using a qualitative descriptive approach with semi-structured interviews, data were collected from selected elementary school teachers who had experience utilizing AI applications in their classrooms. The findings indicate that while teachers recognize the potential of AI in providing interactive and personalized learning experiences, they also encounter barriers such as limited digital literacy, inadequate infrastructure, and lack of training. Nevertheless, teachers demonstrate adaptability by experimenting with AI-supported resources to foster student engagement and independent learning. The study concludes that successful integration of AI in elementary education requires not only teacher readiness and innovation but also institutional support through training, facilities, and curriculum alignment. These insights contribute to a better understanding of how AI can be effectively embedded in elementary education